Modelling hematological parameters after total body irradiation. (July 2014) - Oelkrug, Christopher; Hilger, Nadja; Schönfelder, Uta; Boltze, Johannes; Sack, Ulrich; Fricke, Christian; Hildebrandt, Guido; Keller, Thomas; Emmrich, Frank; Fricke, Stephan
Abstract Purpose: The time- and dose-dependent reconstitution of hematopoiesis after radiation exposure is strongly related to the stem cell population and can be used to predict hematological parameters. These parameters allow further insight into the hematopoietic system and might lead to the development of novel stem cell transplantation models. Materials and methods: CD4-/- C57Bl/6 mice, transgenic for human CD4 and HLA-DR3, were irradiated in a single (3, 6, 8 and 12 Gy) and fractionated (6 × 1 Gy, 6 × 1.5 Gy, 6 × 2 Gy; twice daily) dose regimen. Blood was analyzed weekly for red blood cells (RBC), hemoglobin concentration (Hb), hematocrit (HCT) and white blood cells (WBC). Organ and tissue damage after irradiation were examined by histopathology. Results: The recovery curves for RBC, Hb, HCT and WBC showed the same velocity (< 1 week) for all radiation doses (3–12 Gy) starting at different, dose-dependent times. The only dose-dependent parameter was defined by the beginning of the recovery process (dose-dependent shift) and higher doses were related to a later recovery of the hematopoietic system. The RBC, Hb and HCT recovery was followed by a saturation curve reaching a final concentration independent of the radiation dose. Histological analysis of the bone marrow in the single dose cohort showed a dose-dependent reduction of the cellularity in the bone marrow cavities. The fractioned radiation dose cohort resulted in a regeneration of all bone marrow cavities. Conclusion: Specific functions were developed to describe the reconstitution of hematological parameters after total body irradiation.